ASPECTS OF THE DEVELOPMENT OF MUSICAL SKILLS IN CHILDREN IN THE CONDITIONS OF OUT-OF-SCHOOL EDUCATION - Datsun, Olena (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article considers some aspects of the development of musical abilities of children in the conditions of extra-curricular education. Peculiarities of the organization of group work in out-of-school education institutions, the specifics of communication between pupils and teachers and between children, and the peculiarities of motivation to study are important factors that influence the process of developing musical abilities of children. The purpose of the study: to analyze the regulatory framework that regulates the organization of the educational process in music clubs of extracurricular education institutions, to determine the main aspects of the development of musical abilities in children in the conditions of extracurricular education. The following research methods were used to solve the tasks: analysis of scientific literature; analysis of the regulatory framework; modeling. Results: based on research of the regulatory and legal framework regarding the organization of the educational process in out-of-school education institutions, the educational programs of music clubs, the analysis of the peculiarities of communication between teachers and students, and the motivation of children to learn music, was determined some aspects of the development of musical abilities in children in the conditions extracurricular education. It was determined that the basic part of the educational programs of music clubs includes general educational components: solfeggio, vocal and choral work, playing a musical instrument, concert activity, which are responsible for the development of musical abilities in children regardless of the chosen direction of musical activity. Conclusions: the development of musical abilities in children depends on the peculiarities of the organization of the educational process, which has its own specificity in the conditions of out-of-school education. The process of communication between teachers and students is more formal and performs not only an educational, but also a significant educational function. The specifics of children's motivation to learn music in groups is based on their interest in performing musical activities, positive relationships with peers and teachers, and is positively reinforced by the flexibility of the educational process in the conditions of extracurricular education